2003
DOI: 10.1137/s0363012901379073
|View full text |Cite
|
Sign up to set email alerts
|

An Ergodic Control Problem for Constrained Diffusion Processes: Existence of Optimal Markov Control

Abstract: An ergodic control problem for a class of constrained diffusion processes is considered. The goal is the almost sure minimization of long term cost per unit time. The main result of the paper is that there exists an optimal Markov control for the considered problem. It is shown that under the assumption of regularity of the Skorohod map and appropriate conditions on the drift coefficient the class of controlled diffusion processes considered have strong, uniform in control, stability properties. The stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 50 publications
(54 reference statements)
0
30
0
Order By: Relevance
“…Under these conditions, it follows via the Lipschitz property of the Skorohod map and the usual fixed point arguments that, (1.1) admits a unique strong solution (cf. Theorem 2.6 [8]). If X(·) solves (1.1) then (cf.…”
Section: Condition 25 There Existsmentioning
confidence: 95%
See 4 more Smart Citations
“…Under these conditions, it follows via the Lipschitz property of the Skorohod map and the usual fixed point arguments that, (1.1) admits a unique strong solution (cf. Theorem 2.6 [8]). If X(·) solves (1.1) then (cf.…”
Section: Condition 25 There Existsmentioning
confidence: 95%
“…Under the standing assumptions of this paper there is a unique weak solution for (2.3) and denoting the law of the solution process X(·), when X(0) = x a.s., by P v x it can be shown that {P v x } x∈G is a strongly Feller Markov family (cf. Theorem 2.9 [8]). …”
Section: Definition 27 Let V : G → U Be a Measurable Map We Say Thamentioning
confidence: 95%
See 3 more Smart Citations